Dual-task costs of listening while driving in older and younger adults - Katherine Bak; Kristen Arnold; Lena Darakjian; M. Kathleen Pichora-Fuller; Frank A. Russo; Jennifer L. Campos (PLoS ONE, 2025)
Age-related changes in hearing and cognition result in increased listening difficulties, which could affect the ability to perform common, complex, multitasking behaviours, such as listening while driving. However, there are very few realistic and controlled studies examining how the competing attentional demands of listening while driving affect performance and how performance may differ between younger and older adults. The primary objective of this study was to examine dual-task costs of listening while driving in older (N = 24, Mage = 68.29 years, 15 female) and younger (N = 24, Mage = 26.42 years, 12 female) licensed drivers with normal hearing, vision, and cognition. Participants completed a driving task in a high-fidelity driving simulator during simpler (Rural driving) and more complex (City driving) driving conditions. They also completed the Connected Speech Test (CST) at +4 signal-to-noise ratio (SNR; easier listening) and at 0 SNR (harder listening) conditions. Finally, they completed both tasks simultaneously to examine the dual-task costs of listening while driving. Results demonstrated that only older adults showed significantly poorer listening accuracy on the CST in the dual-task compared to the single-task condition, particularly during the more difficult driving conditions (City driving). Both older and younger adults showed poorer driving performance (greater variability in lane position) in the dual-task compared to the single-task condition, which was most pronounced under the most challenging conditions (City driving, 0 dB SNR listening). However, the magnitude of these dual-task costs during the most challenging conditions was greater in older adults than younger adults. Findings may inform mitigation strategies to reduce the effects of difficult listening conditions on driving performance by optimizing vehicle acoustics or by minimizing auditory distractions, particularly during more challenging driving conditions.